The Quasi-lattice of Indiscernible Elements - Nascimento, Mauri Cunha do [UNESP]; Krause, Decio; Feitosa, Hércules de Araujo [UNESP] (Springer, 2011)
The literature on quantum logic emphasizes that the algebraic structures involved with orthodox quantum mechanics are non distributive. In this paper we develop a particular algebraic structure, the quasi-lattice (J-lattice), which can be modeled by an algebraic structure built in quasi-set theory sic. This structure is non distributive and involve indiscernible elements. Thus we show that in taking into account indiscernibility as a primitive concept, the quasi-lattice that 'naturally' arises is non distributive.
Keywords: lattice of indiscernibles; quasi-sets; quantum logic